Perencanaan Perkerasan Lentur Ruas Jalan Pao - Pao – Bajimangai Maros - Filadelfia Natasha Tiku (Paulus Civil Engineering Journal, 2025)
The Pao-Pao - Bajimangai road improvement is an activity to overcome the problems complained about by the Bajimangai community, where the road axis is an alternative route for the community to Kariango. The research was conducted by planning to design the thickness of flexible pavement using the Component Analysis method and the 2024. The design pavement thickness 3 results include a 30 mm thick HRS-WC surface layer, 35 mm thick HRS-Base, a class 150 mm thick for the upper foundation layer and 125 mm for the lower foundation layer with LPA class B. The design 3A consists of a 40 μm thick AC-WC surface layer, a 60 μm thick AC-BC layer, and a 400 μm thick Class A top layer. A 50 mm thick melting layer, 150 mm thick crushed stone, and 100 mm thick sandy soil were obtained using the Component Analysis method. The class A Top Foundation Layer is 30 mm thick, the HRS-WC surface layer is 30 mm thick, the HRS-Base is 35 mm thick, and the bottom foundation layer uses 125 mm thick class B LPA.